2001
DOI: 10.1074/jbc.m103236200
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of the Mammalian Mitochondrial Ribosome

Abstract: The mammalian mitochondrial ribosome (mitoribosome) has a highly protein-rich composition with a small sedimentation coefficient of 55 S, consisting of 39 S large and 28 S small subunits. In the previous study, we analyzed 39 S large subunit proteins from bovine mitoribosome (Suzuki, T., Terasaki, M., Takemoto-Hori, C., Hanada, T., Ueda, T., Wada, A., and Watanabe, K. (2001) J. Biol. Chem. 276, 21724-21736). The results suggested structural compensation for the rRNA deficit through proteins of increased molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(41 citation statements)
references
References 66 publications
1
39
1
Order By: Relevance
“…We have not observed any peptides from this small protein in 28 S or 39 S subunit preparations. This group has further reported that a subunit (CI-B14) of NADH-ubiquinone oxidoreductase (Complex I) is present in preparations of 55 S ribosomes (36). However, we have not observed peptides from this protein in either 28 S or 39 S subunit preparations.…”
Section: The New Classes Of Ribosomal Proteins With Homologs In Yeastcontrasting
confidence: 41%
“…We have not observed any peptides from this small protein in 28 S or 39 S subunit preparations. This group has further reported that a subunit (CI-B14) of NADH-ubiquinone oxidoreductase (Complex I) is present in preparations of 55 S ribosomes (36). However, we have not observed peptides from this protein in either 28 S or 39 S subunit preparations.…”
Section: The New Classes Of Ribosomal Proteins With Homologs In Yeastcontrasting
confidence: 41%
“…An intramitochondrial pool of DAP3 apparently operates as a subunit of the mitochondrial ribosome, presumably involved in the translation of mitochondria genome-derived transcripts (23)(24)(25), whereas an extramitochondrial pool of DAP3 participates in apoptosis signaling within the extrinsic pathway (5-7). Unlike cytochrome c, however, there is no evidence thus far that DAP3 must be released from mitochondria to perform its cell death function (10).…”
Section: Discussionmentioning
confidence: 99%
“…In human mitochondria, only 42 of 54 E. coli r-protein orthologues and also many mitochondria-specific r-proteins are detected (O'Brien, 2003). Such mitochondria-specific rproteins appear to be involved in ribosome-specific functions besides translation, such as the involvement of DAP3 in apoptosis (Suzuki et al, 2001a).…”
Section: Review 2002mentioning
confidence: 99%